2008
DOI: 10.1159/000119520
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Association between Fluoride Intake and Dental Fluorosis in Permanent Teeth

Abstract: Objective: To evaluate the relationship between fluoride intake and dental fluorosis in permanent central incisors and first molars. Methods: Fluoride intake (mg F/kg body weight/day) from diet, dentifrice and both combined was determined on a single occasion in 1998 among children aged 19–39 months living in two fluoridated Brazilian communities (0.6–0.8 ppm F). Six years later, when the permanent teeth of these children had erupted (central incisors and first molars), 49 children aged 7–9 years [20 girls (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 79 publications
1
33
0
8
Order By: Relevance
“…26 Furthermore, a study estimating F intake either from diet, or dentifrice or a combination of both for children with and without DF, found a similar F intake for both groups of children. 27 An association between a higher frequency of tooth brushing and fluorosis was detected in this study, in agreement with other studies. 20,28 Although the frequency of tooth brushing was not precise, it was used as a proxy measurement for the amount of F toothpaste being ingested, 26 insofar as higher frequencies of tooth brushing are expected to increase the risk of F intake.…”
Section: Discussionsupporting
confidence: 93%
“…26 Furthermore, a study estimating F intake either from diet, or dentifrice or a combination of both for children with and without DF, found a similar F intake for both groups of children. 27 An association between a higher frequency of tooth brushing and fluorosis was detected in this study, in agreement with other studies. 20,28 Although the frequency of tooth brushing was not precise, it was used as a proxy measurement for the amount of F toothpaste being ingested, 26 insofar as higher frequencies of tooth brushing are expected to increase the risk of F intake.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, Burt 2 suggested in 1992 that a daily dose of 0.07 mg F per kg of body weight should be taken as the upper limit, so that the resultant fl uorosis would not compromise the anti-caries benefi ts from fl uoride intake among children within the at-risk age group. However, this limit should be validated by data from a longitudinal dose-effect study, and no association between the dose and the resultant fl uorosis has been found 16 , requiring more studies about a safety dose.…”
Section: Water Potability and Fluoride Concentrationmentioning
confidence: 99%
“…As a result of the development of various fl uoride products for individual and collective use, there has been an increase in the prevalence of dental fl uorosis 6 . Among these products, fl uoride toothpastes are used by children during tooth development.…”
Section: Introductionmentioning
confidence: 99%